2018
DOI: 10.1016/j.margeo.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Dating the Cooloola coastal dunes of South-Eastern Queensland, Australia

Abstract: The Cooloola sand dunes are part of a series of aeolian parabolic dunes that stretch along the east coast of Australia. They form a chronosequence showing increasing weathering, soil formation and water erosion across six geomorphically recognized soil landscapes. These landscapes were recognized from air photographs and further refined on the basis of some 150 auger holes across the dunes. Data about the structure and floristics of the vegetation were collected at the same time. There is a significant body of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 62 publications
6
46
0
Order By: Relevance
“…Ward (2006) recognised nine periods of dune building based on soil development and morphological characteristics. More recently, Walker et al (2018) identified 10 units at the Cooloola Sand Mass and used single grain optically stimulated luminescence (OSL) dating to identify periods of activity. They found that the oldest units at Cooloola date to about 725 ka, confirming earlier work by Tejan-Kella et al (1990) and they also observed that dune emplacement has continued episodically.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Ward (2006) recognised nine periods of dune building based on soil development and morphological characteristics. More recently, Walker et al (2018) identified 10 units at the Cooloola Sand Mass and used single grain optically stimulated luminescence (OSL) dating to identify periods of activity. They found that the oldest units at Cooloola date to about 725 ka, confirming earlier work by Tejan-Kella et al (1990) and they also observed that dune emplacement has continued episodically.…”
Section: Study Sitementioning
confidence: 99%
“…More recently, the dune fields have become the focus of renewed geochronological (e.g. Brooke, Pietsch, Olley, Sloss, & Cox, 2015;Walker, Lees, Olley, & Thompson, 2018) and paleoenvironmental investigations (e.g. Barr et al, 2013;Cadd et al, 2018;Chang et al, 2015;Levin, 2011;Levin, Jablon, Phinn, & Collins, 2017;Moss, Tibby, Petherick, McGowan, & Barr, 2013;Petherick, McGowan, & Moss, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These sediments are sourced from the Triassic Hawkesbury Sandstone unit located in the Sydney Basin (Wasantha and Ranjith, 2014) and are mostly quartz with ,2% heavy minerals and little to no carbonate (Thompson, 1983). The CSM is suggested to be one of the world's oldest continuous coastal dune fields according to thermoluminescence dating of sand grains, revealing an age of 700 ka (Tejan-Kella et al, 1990;Walker et al, 2018). The mostly open coast shorelines of the study area are wave-dominated and microtidal (Harris et al, 2002) and are influenced by a variety of synoptic weather patterns that operate in and around the neighboring Coral Sea (Harley et al, 2010).…”
Section: Study Sitementioning
confidence: 97%
“…Much of the undulating form of the coastal sand plain was created in the Pleistocene as indicated by a core taken from a lowlying peat swamp (Carlo Creek) located 1.5km inland which revealed ~22,000 year old sandy deposits at a depth of 3m (Krull et al 2004:414). The potential for older Pleistocene landforms across the coastal sand plain is indicated by the interfingering of Cooloola sandmass Dune System 7 dating (OSL) to ~700,000 years ago across the eastern parts of the plain (Walker et al 2018). These interfingerings form drainage lines that empty into the inlet indicating that much of the meandering form of the east coast of the inlet is a relic of Pleistocene drainage patterns (Krull et al 2004:413).…”
Section: Palaeoenvironments and Formation Of The Inletmentioning
confidence: 99%